Aerodynamic Performance Evaluation of Contemporary Passenger Vehicle Designs Using CFD - Li Chuhui; Hidayatullah Mohammad Ali (International Journal of Integrated Engineering, 2026)
Modern automotive design faces the challenge of reducing aerodynamic drag while meeting strict environmental standards and maintaining practicality, aesthetics, and efficiency in electric vehicles. This study investigates the aerodynamic performance of various vehicle body designs using Computational Fluid Dynamics (CFD) simulations, aiming to assess how design modifications influence drag reduction and pressure distribution across critical surfaces. Simulations were conducted at various speeds to evaluate the aerodynamic behavior of each design, focusing on the drag coefficient and pressure values in key areas such as the front end, windshield, roof, and rear section. Results showed that one configuration achieved a significant improvement in aerodynamic efficiency, with the drag coefficient reduced to 0.273 at 30 km/h and further to 0.259 at 120 km/h, demonstrating stable performance at both low and high speeds. Pressure values in critical regions also dropped substantially, with front-end pressure decreasing by more than 60% compared to other models. These reductions in aerodynamic resistance correlate directly with improved energy efficiency, benefiting both fuel-powered and electric vehicles. Notable aerodynamic improvements stemmed from smoother body contours, optimized roof curvature, and proportioned dimensions that enhance airflow and reduce turbulence. These design elements minimize flow separation and wake formation, resulting in reduced drag forces and better vehicle stability. This research underscores the importance of incorporating aerodynamic principles early in vehicle design, offering valuable insights for the development of energy-efficient, environmentally responsible vehicles and a practical framework for future automotive advancements.